Digital Native Generation Strategies in Handling the Spread of Hoax News by Parents on Social Media - Adhiani Nur Arifah; Siti Nurbayani; Rama Wijaya Abdul Rozak (Jurusan Ilmu Komunikasi UTM, 2023)
The problem regarding the spread of hoax news has not been thoroughly handled until now, especially on social media. The flow of information circulation is very rapid, forcing people to have a deeper understanding and ability to filter news that is widespread in cyberspace. The problem is, not all people can understand this, especially for groups of people who are just getting used to using technology such as parents. Therefore, it takes the role of digital natives to be able to control and educate parents. In a family environment, someone who has a role as a native is a child. So this research will examine more deeply the role of a child as a digital native in educating his parents about hoax news. This study uses qualitative methods and a phenomenological approach. The results of the study state that there are 2 core stages when a child carries out digital education to his parents, namely the identification and confrontation stages. As for the implementation of educational efforts, a child highly upholds manners and respects the position of parents